JAPANESE STUDENTS’ MINDSET AND MOTIVATION IN STUDYING ENGLISH GRAMMAR AND READING - Ocampo, Merissa (PEOPLE: International Journal of Social Sciences, 2017)
This study probes the intrinsic and extrinsic types of the motivation of Japanese University students and sheds light on their mindset and beliefs about learning English Grammar and Reading. During 2016, a survey was administered to 260 students at a University in Tohoku, Japan. The findings revealed that 73% of participan0ts tended to have a fixed mindset with a slight degree of growth mindset while 19% tended to favor a growth mindset with some degree of fixed mindset, 6% with a strong fixed mindset and 2% with a strong growth mindset. This suggests that these students need to be motivated to be more pro-failure and accepting of mistakes to succeed in learning English. During this research, the author also taught with the support of the Family Environment Mode Approach (FEMA) (Ocampo, 2015). The study confirmed that the FEMA approach promoted a feeling of relaxation in at least half the participants during classroom activities, despite the pressures they were facing due to Test of English for International Communication(TOEIC) examination preparation. 98% of these students were also found to be extrinsically motivated in learning English grammar and reading, as they were included in their curriculum.